Frames that describe people in fictional discourse - Kozak, Sofia V.; Козак, Софія Веніамінівна (Східноєвропейський національний університет імені Лесі Українки, 2014)
The research paper is dedicated to the investigation of the peculiarities of the functioning and verbal filling of the frame structures that describe people in German fictional discourse represented by the novel “Jephthah and his daughter” [“Jefta und seine Tochter”] by Lion Feuchtwanger. The research of a literary discourse implies the interpretation of its content with the regard of its micro- and macrostructure, i.e. its inner and outer relations, linguistic and extra-linguistic contexts. At the same time it is necessary to investigate questions which are directly connected with functional pragmatics of a discourse, namely the questions of the frame representation. The term frame got into the branch of linguistics from the cognitive psychology and became a distinctive contact link between language structures and their correlates in the reality. Being actualized and mobilized by the authors, frames form a discourse, define its quality and pragmatics. The analysis of the lexical units that describe people‟s appearance in the novel “Jephthah and his daughter” by L. Feuchtwanger made it possible to research cognitive-pragmatic features of the frame structures which represent the frame „Appearance‟ in the fictional discourse. The analyzed extracts of the literary work represent interesting examples of the frame structures, which describe human appearance. The terminal elements, which represent people‟s features, play an important part in the verbal presentation of the frame „Man‟, because they help the author to express the nature of the main characters of the novel as well as to reveal their inner world. Статтю присвячено важливій проблемі когнітивної лінгвістики – дослідженню функціонування фреймових структур, що описують зовнішність людини в літературно-художньому дискурсі на прикладі фрейму “ЗОВНІШНІСТЬ” у романі німецького письменника Ліона Фейхтвангера “Ієфай та його дочка”. Фреймову структуру визначаємо як об‟єднання лексико-синтаксичних одиниць, що представляють відповідні фрейми в дискурсі та пов‟язані спільною участю в актуалізації авторської прагматики. Визначено основні термінали, що належать до фрейму “ЗОВНІШНІСТЬ”, та проаналізовано лексичні одиниці, що представляють його термінали. Досліджено когнітивно-прагматичні особливості фреймових структур, що описують зовнішність людини в німецькомовній художній прозі. Аналіз довів, що фреймові структури, які описують зовнішність людини, – ефективний механізм експлікації авторських думок не лише щодо зовнішнього вигляду персонажів, але і їхніх характерів, і внутрішнього світу.
Фрейми опису людини в художньому дискурсі
Keywords: discourse; frame; frame structure; terminal; terminal element; appearance; дискурс; фрейм; фреймова структура; термінал; термінальний елемент; зовнішність